Evaluación química y bromatológica de las dosis de lactobacillus plantarum en la producción de ensilajes de zapallo (cucurbita máxima) y yuca (manihot esculenta) - Varela Muñoz, José Gregorio (2016)
The objective of this research was to evaluate the chemical and physical effects of different doses of Lactobacillus plantarum in the ensiling process of squash (Cucurbita máxima) and manioc (Manihot esculenta) for fermentation improvement. We used 1%, 2% and 3% of Lactobacillus plantarum content as treatments. Percentages correspond to fractions of a homogeneous mix composed of molasses, water, and squash and manioc wastes. We used a Randomized Complete Block design (RCB) using six treatments, each with three replications. The fermentation process was accomplished under anaerobic conditions, and lasted for 25 days. The chemical variables evaluated were as follows: Titratable acidity on different fermentation days (1, 12 and 25) in order to identify the presence of lactic acid, and pH level, which was measured on days 1 and 25. As bromatological variables, we included moisture content, ash, fiber, protein, fat, carbohydrates, total energy and hydrocyanic acid in the ensiling process of manioc wastes. Bromatological variables were measured on day 25 of the fermentation process. After data analysis, 2% Lactobacillus plantarum. This was determined in relation to microorganism response during the fermentation process through the assessment chemical of pH-related (a1b2 = 4,01 y a2b2 = 4,11) and acidity (a1b2 = 5,36 y a2b2 = 6,24) and through the presence of anti-nutrients in both ensiling processes.